Clinical and Imaging Characteristics of Spinal Dural Arteriovenous Fistulas and Spinal Epidural Arteriovenous Fistulas. Issue 3 (11th March 2021) - Brinjikji, Waleed; Colombo, Elisa; Cloft, Harry J; Lanzino, Giuseppe
Abstract: BACKGROUND: Spinal epidural arteriovenous fistulas (SEDAVFs) are an increasingly recognized form of spinal vascular malformation and are distinct from spinal dural arteriovenous fistulas (SDAVFs). Differentiating between these 2 entities is important as operative strategies often differ based on angioarchitecture. OBJECTIVE: To compare demographic, clinical, anatomic, and imaging findings of SDAVFs and SEDAVFs. METHODS: Consecutive patients diagnosed and/or treated for SDAVF or SEDAVF at our institution between January 2000 and November 2018 were included. Data were collected on demographics, clinical presentation, and imaging findings. All cross-sectional and angiographic imaging were reviewed. To compare continuous variables, t -test was used Chi-squared was used for categorical variables. RESULTS: A total of 169 patients were included. In total 47 patients had SEDAVFs and 122 patients had SDVAFs. Clinical presentation and magnetic resonance imaging (MRI) imaging findings were similar between the 2 groups. SEDAVF patients were significantly more likely to have an epidural venous pouch on gadolinium bolus MR angiography (MRA) (0.0% vs 92.1%, P  < .0001). SEDAVFs were more commonly located in the lumbar and sacral spine than SDAVFs (85.1% vs 34.4%, P  < .0001). When in the lumbar spine, SEDAVFs unlike SDAVFs were more likely to involve the most caudal segments (L4 and L5, P  = .02). CONCLUSION: SEDAVF share clinical and radiological findings similar to SDAVFS, including high T2 cord signal, cord enhancement, and perimedullary flow voids on conventional MRI. However, they have a characteristic appearance on spinal MRA and DSA with a pouch of epidural contrast. SEDAVFs are more commonly located in the lumbosacral spine.